2006
DOI: 10.1177/002242940605400106
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Instrumental Music Participation and Socioeconomic Status on Ohio Fourth-, Sixth-, and Ninth-Grade Proficiency Test Performance

Abstract: This study is a comparison of the Ohio Proficiency Test (OPT) results of instrumental music students and their noninstrumental classmates according to socioeconomic status (SES) over time. Subjects ( N= 15,431) were students in the Columbus Public Schools in Ohio, whose fourth-, sixth-, and ninth-grade OPT results were compared with others of like SES on the subjects of citizenship, math, science, and reading. Results show that instrumental students outperformed noninstrumental students in every subject and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
95
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 11 publications
17
95
0
6
Order By: Relevance
“…These results are congruent with similar studies showing a positive correlation between music participation and standardized test scores (The College Board & MENC, 2001;Babo, 2004;Vaughn & Winner, 2000;Kluball, 2000;Helmrich, 2010). Many studies concluded that music was beneficial for all students regardless of their socioeconomic status (Catterall, 1998;Kinney, 2008;Miksza, 2007;Fitzpatrick, 2006).…”
Section: Chapter I -Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are congruent with similar studies showing a positive correlation between music participation and standardized test scores (The College Board & MENC, 2001;Babo, 2004;Vaughn & Winner, 2000;Kluball, 2000;Helmrich, 2010). Many studies concluded that music was beneficial for all students regardless of their socioeconomic status (Catterall, 1998;Kinney, 2008;Miksza, 2007;Fitzpatrick, 2006).…”
Section: Chapter I -Introductionsupporting
confidence: 82%
“…In addition, recent studies that focus on achievement in the "high-stakes" Helmrich, 2010). Many studies concluded that music was beneficial for all students regardless of their socioeconomic status (Catterall, 1998;Kinney, 2008;Miksza, 2007;Fitzpatrick, 2006).…”
Section: Chapter I -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the data, Fitzpatrick (2006) and Johnson and Memmott (2006) reinforce the stance that music instruction should be offered in the schools for music's sake alone. Kinney and Forsythe (2005) acknowledge that music educators prefer to establish music in the schools for its intrinsic qualities, yet recognize that this position can often require a little bending to yield to the political and other pressures placed upon them.…”
Section: The Extra-musical Benefits Of Music Instructionmentioning
confidence: 94%
“…For instance, Zellner (2011) found a positive relationship between instrumental music instruction and critical thinking skills as assessed by the math and reading content areas of the Pennsylvania System of School Assessment. Fitzpatrick (2006) evaluated the test scores of Columbus, Ohio students on all areas of the Ohio Proficiency Test. Instrumental students of both socioeconomic statuses outperformed their non-instrumental peers with instrumental students receiving free and reduced price lunches outperforming the non-instrumental students at the higher economic status on four of five content areas, an interesting trend worthy of note.…”
Section: The Extra-musical Benefits Of Music Instructionmentioning
confidence: 99%